2021
DOI: 10.1371/journal.pone.0246330
|View full text |Cite
|
Sign up to set email alerts
|

Delirium as a predictor of mortality and disability among hospitalized patients in Zambia

Abstract: Objective To study the epidemiology and outcomes of delirium among hospitalized patients in Zambia. Methods We conducted a prospective cohort study at the University Teaching Hospital in Lusaka, Zambia, from October 2017 to April 2018. The primary exposure was delirium duration over the initial 3 days of hospitalization, assessed daily using the Brief Confusion Assessment Method. The primary outcome was 6-month mortality. Secondary outcomes included 6-month disability, evaluated using the World Health Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the inpatient setting, limited access to basic critical care resources and neurologic expertise means that most neurologic emergencies are managed on low-acuity wards by staff who have received limited focused training in care for acute neurological disease (Dart et al, 2017;Norrving et al, 2018;Banerdt et al, 2021). The care of patients with AND can vary considerably between countries and between healthcare settings due to local epidemiology, affordability of care, health system financing, and resource availability (Prust et al, 2022).…”
Section: Assessment Of Policy/guidelines Options and Implicationsmentioning
confidence: 99%
“…In the inpatient setting, limited access to basic critical care resources and neurologic expertise means that most neurologic emergencies are managed on low-acuity wards by staff who have received limited focused training in care for acute neurological disease (Dart et al, 2017;Norrving et al, 2018;Banerdt et al, 2021). The care of patients with AND can vary considerably between countries and between healthcare settings due to local epidemiology, affordability of care, health system financing, and resource availability (Prust et al, 2022).…”
Section: Assessment Of Policy/guidelines Options and Implicationsmentioning
confidence: 99%
“…They found that 41.1% of patients with altered mental status upon admission died within the first 48 h, and only 10.8% survived beyond 30 days. Utilizing RS that encompass intrinsic patient traits, clinical indicators and lab results could identify those at elevated risk of long-term mortality from lower respiratory tract infections [ 11 , 13 ]. Yet, evidence concerning the utility of clinical variables and RS in CAP patients remains sparse, given the limitations of long-term mortality studies [ 11 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimated community dementia prevalence is 2-6.4% and hospital prevalence 3-5% [9][10][11]. One Zambian delirium study reported a hospital prevalence of 48.5% and that delirium duration independently predicted mortality and disability at 6 months in all age groups [12]. Studies in older populations are even more limited.…”
Section: Introductionmentioning
confidence: 99%